MANAJEMEN PENDIDIKAN KESETARAAN PAKET C DI LEMBAGA PEMASYARAKATAN - Suharjudin Suharjudin (Jurnal Manajemen Pendidikan, 2012)
The objectives of this research was to understand comprehensively the management of education implemented in the package C equivalent education. It was a qualitative research with a case study method (explanatory case study) conducted in Class IIA Prison of Bekasi in 2012. Focus of this research was management of education in package C equivalent education with three sub focuses. They are: mechanism of planning, mechanism of decision making and process of team work. The data were collected through participant observation using interview, observation, document study, and recording. The data analysis and interpretation indicates that (1) planning is arranged with coordination of both team work, but the authorities in charge to formally design the plans is SKB Kab. Bekasi, the panning used short range/short term planning which more focus on operational study and directional. The plan was a standing plan; (2) decision making process used group decision making, where mostly driven by consensus of both team work with a very simple way, not time consuming, relax situation and without intervention of both head of institution; (3) team work is formed formally by joint team work consist of representative of SKB and Class IIA Prison of Bekasi, team work run effectively due to very rare conflict found; the team had 1 year pre-relationship before it formed officially, this made the team very dynamic, tolerance. The findings lead to recommendation to maintain this joint team work in order to the sustainable package C equivalent education will still continue. It’s also recommended that some improvement needs tobe taken.